English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6 answers

If x = cosy, then y = cos^-1 x
y=cos^-1 x
y' = -1/√(1-x^2)

2007-03-09 18:19:05 · answer #1 · answered by Anonymous · 0 3

you're taking the by-product with appreciate to x => dy/dx Use implicit differentiation simply by fact the variable dont agree. Use the product rule one the left facet two times to distinguish and whenever you diff in terms of y(the var doesnt agree) incorporate dy/dx. Then set up the words so as that on the left you have each and every thing that includes (dy/dx) take it as an undemanding element so u can remedy for it. flow the term it is multiplying dy/dx to divide on the different facet of the equation. Voula permit me be responsive to in case you prefer a worked out answer

2016-10-18 00:30:44 · answer #2 · answered by ? 4 · 0 0

start with x = cosy
differentiate with respect to x , treat y as function of x so y = y(x)

you will get immediatly
1 = siny * dy/dx
( dx/dx = 1 , and dcosy/dx = -siny * dy/dx well as i said immediatly chain rule ... )

)

so -1/siny = dy/dx.

2007-03-09 19:59:36 · answer #3 · answered by gjmb1960 7 · 0 0

implicit differentiation:

x = cos ( y )

dx = - sin ( y ) dy

dy/dx = - sin ( y )

___________________________

If you want to express dy/dx in terms of x,
use the trig identity cos^2 (y) + sin^2 (y) = 1

So
sin^2 ( y ) = 1 - cos^2 ( y )

Substituting:

sin^2 ( y ) = 1 - x^2

-sin (y) = - sqr ( 1 - x^2 )

So

dy/dx = -sqr ( 1 - x^2)

2007-03-09 18:39:28 · answer #4 · answered by Hk 4 · 0 1

this should be =====> (x)' = (cos y)'

(x)' = 1

(cos y)' = -sin(y) * (y)' as the chain rule says....

then dy/dx=1/-sin(y)= - csc (y)

2007-03-09 18:28:03 · answer #5 · answered by A New Life 3 · 0 2

x = cosy
1=dy/dx(-siny)
dy/dx=1/(-siny)
dy/dx=-1/√(1-x^2)

2007-03-09 18:20:18 · answer #6 · answered by Anonymous · 2 2

fedest.com, questions and answers